(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Fossil fuels, coal in particular, are indispensable sources of energy necessary for today’s technological and economical progress throughout the world. Their burning releases numerous environmental contaminants, like CO2, SO2, and a range of organic and inorganic compounds. Arguably, however, and despite the fact that these emissions have resulted in air pollution and regional acid rain problems, there is no evidence yet of their usage completely replaced by a low-CO2–producing energy source. Coal, due to its unique composition and characteristics, has been actively investigated by scientists and technologists from various disciplines in a search for economically valuable metals and medically active substances. Also, coal is used universally for the fabrication of new nanomaterials in laboratories, and utilized in waste-treatment and clean-coal technologies. The aim of the paper was to focus on the latest advancements in coal research of leading international scientists from India, China, and USA. Also, the paper is briefly presenting selected papers of several Indian and Croatian research groups addressing environmental issues and emerging waste-treatment technologies. Although the two countries are different from the geographical, historical, economical, and industrial point of view, the both have been linked with the coal extraction and its usage in power generation and associated heavy industries.